Competition in Austrian Treasury Auctions - Christine Zulehner; Helmut Elsinger; Philipp Schmidt-Dengler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate the role of competition on the outcome of Austrian Treasury auctions. EU accession by Austria provides a natural experiment causing an exogenous increase in the number of bidders in Treasury Auctions. Difference-in-difference estimates suggest that the increased number in bidders caused a significant drop in the yields Austria had to pay for newly issued debt. We use structural estimates of bidders private values to examine the effect of increased competition on auction revenue. We compare bidder surplus before and after the auction. We find a small effect on the the surplus earned by bidders as a result of increased competition.
Keywords: D44; L13; G12; 330